PTH-048 Diagnostic ERCP in specialist centres: safe and effective for evaluating indeterminate biliary changes following MDT. (8th June 2018) - On, Wei; Dwyer, Laura; Saleem, Rizwan; Hood, Steve; Sturgess, Richard; Stern, Nick
Abstract : Introduction: Indeterminate biliary strictures (BS) may be identified in symptomatic patients or incidentally on imaging. Patients need investigation to exclude cholangiocarcinoma or other significant pathology. The first line investigation is with Magnetic Resonance Cholangio-Pancreatography (MRCP) however this is not always diagnostic. Such cases are all reviewed through our tertiary Multi-disciplinary team (MDT) meeting for further evaluation. Diagnostic Endoscopic Retrograde Cholangio-Pancreatography (ERCP) is often used to further investigate these abnormalities 1 but carries a risk of complications. Methods: A retrospective analysis was performed of patients reviewed through our regional HPB MDT from October 2014 to December 2016. Patients with indeterminate BS with no mass lesion were identified from our MDT database. Following MDT discussion, all patients were investigated with ERCP ±cholangioscopy (POC). Liver Function Tests (LFTs) and details of suspected BS were obtained from the medical records. Diagnoses were obtained from the endoscopy database and histopathology reports, where applicable. Results: 66 patients were identified with a mean age of 63.7 (SD 14.5). 47% were male. 82% of patients had abnormal LFTs, 35% had jaundice and 61% had upstream dilatation on radiological imaging. 31 (47%) required POC in addition to ERCP. 85% of patients (n=56) had an abnormal diagnosis. 8 (12.1%) had malignancy, 13 (19.7%) PSC or other cholangiopathy and 10 (15.2%) stone disease. In our centre, complications associated with these ERCPs were low: pancreatitis: 1 (1.6%); cholangitis: 1 (1.6%); bleeding:1 (1.6%). There were 2 delayed bleeds (peptic ulcer and variceal). Upstream dilatation was shown to be a predictor of abnormal diagnosis on both univariate (p=0.004) and multivariate analysis (p=0.01) with a sensitivity of 72.5%, specificity of 72.7%, positive predictive value of 92.5% and negative predictive value of 36.4%. Conclusions: Of those with suspected BS on imaging, 85% had pathology demonstrated on direct cholangiography ±POC. 15.2% of those reviewed through a tertiary HPB MDT had stone disease evident at ERCP that was not diagnosed on review of MRCP and other imaging modalities. Diagnostic ERCP in appropriate centres still has a role to play in the evaluation of indeterminate biliary strictures following specialist MDT review when non-invasive imaging is inconclusive. Reference: . British Society of Gastroenterology. ERCP – the way forward, A Standards Framework 2014. https://www.bsg.org.uk/resource/ercp—the-way-forward–a-standards-framework-pdf.html